Decision Support System for Determining the Best Santri Using the SAW Method: Sistem Pendukung Keputusan Penentuan Santri Terbaik Dengan Metode SAW - Malik, Kamil; Sya’roni, Wahab (Universitas Muhammadiyah Sidoarjo, 2022)
The I'dadiyah Az-zainiyah institution is an institution devoted to new students of the Nurul Jadid Islamic Boarding School Paiton Probolinggo at the junior and senior high school levels. This institution is devoted to new students who do not have a foundation in religion. To give appreciation to the students of the I'dadiyah Az-zainiyah Institute so that Santi is more enthusiastic to study religious knowledge every semester, the best students will be selected to be awarded in the form of scholarships. However, from the large number of participants, the management of the I'dadiyah Az-zainiyah Institution has difficulty determining the best participants because there are several variables that must be compared between one santri and another, so there is often a delay in the announcement of the best participants which results in delays in prospective students who get scholarships. from several schools under the auspices of the Nurul Jadid Islamic Boarding School. Seeing this, it is necessary to have a method that can make it easier for the administrators of the I'dadiyah Az-zainiyah Islamic Boarding School Nurul Jadid to determine the best new students or new students. The method taken by the researcher is the Simple Additive Weighting (SAW) decision support system method.